In vitro activity of zoliflodacin (ETX0914) against macrolide-resistant, fluoroquinolone-resistant and antimicrobial-susceptible Mycoplasma genitalium strains. (12th February 2018) - Damião Gouveia, A C; Unemo, M; Jensen, J S
Abstract: Background: Mycoplasma genitalium is estimated to be the second most common cause of bacterial sexually transmitted infection in Europe. It is of increasing public health concern due to the rapid development of resistance to different antimicrobial classes, including the preferred first- and second-line treatments azithromycin and moxifloxacin. Thus, new antimicrobial agents are urgently needed, especially for the treatment of MDR strains. Methods: The in vitro activity of the new spiropyrimidinetrione zoliflodacin against 47 M. genitalium strains was assessed by growing M. genitalium in Vero cell culture and measuring growth by quantitative PCR. The collection included 34 moxifloxacin-susceptible (MIC <1 mg/L) and 13 moxifloxacin-resistant (MIC ≥1 mg/L) strains. Twenty-three of the strains were azithromycin resistant (MIC ≥16 mg/L) and 12 of these strains were MDR. Results: Only one (2.1%) strain with substantially increased MIC (4 mg/L) and potential resistance to zoliflodacin was found. Zoliflodacin was overall more potent than moxifloxacin ( P = 0.009) and no cross-resistance was observed between the two drug classes of topoisomerase II inhibitors. Differences in the MICs of zoliflodacin and azithromycin were not statistically significant; however, 23 (48.9%) compared with potentially 1 (2.1%) of the strains were resistant to azithromycin and zoliflodacin, respectively. Conclusions: Zoliflodacin is a promising candidate for the treatment of M. genitalium and it is important to further develop and evaluate this drug.